Law Enforcement Implementation Against Domestic Violence - I Dewa Made Sarwa Mandala; Sri Endah Wahyuningsih (Universitas Islam Sultan Agung, 2020)
In essence, domestic violence is not only contrary to Pancasila as a source of law in Indonesia, it is also against the 1945 Constitution of the Indonesian State. The formulation of the problem in this research is: the causes of the Crime of Domestic Violence (DV) which hinders the Criminal Law Policy in tackling the Crime of Domestic Violence (DV) and the Implementation of Law Enforcement of the Crime of Domestic Violence (DV). The method used is a sociological juridical legal approach and the specifications in this study include descriptive analytical. The sources and types of data in this study are primary data. And secondary data obtained from literature studies related to theory of Law Enforcement and Legal System. Based on the results of that research A patriarchal culture that places men as superior beings and women as interior creatures; Incorrect understanding of religious teachings so that men can dominate women; The imitation of a boy who lives with a beating father will usually imitate his father's behavior. Different understandings between law enforcers on Domestic Violence (DV); The length of time between the incident and the post mortem, so that the post mortem results are less supportive of the legal process; Cases reported by victims are often not followed up, because victims are doubtful or do not understand that what is being reported is a criminal act. By means of preemptive efforts, carried out by the police to prevent criminal acts. Preventive measures are also carried out as follow-up efforts to pre-emptive efforts that are still at the level of prevention before the occurrence of crimes. As well as repressive measures are carried out when there has been a crime / crime in which the action is law enforcement by imposing a sentence.